Understanding the governance and inheritance mechanism of Fujian merchants from the perspective of modern economics - ZHANG, Feiyan (Institutional Knowledge at Singapore Management University, 2024)
Under the general background of globalization and market economy, Chinese enterprises are embracing advanced governance models around the world, and facing the challenge of effectively combining them with local culture. In the history of China, Fujian (Min) merchants formed a famous commercial group, leaving modern enterprises some precious enlightenment in its unique governance and inheritance mechanism. This research will extensively explore the governance mechanism of Fujian commercial group and assess its potentials and enlightenment for application in the system of modern enterprises. This research aims to provide theoretical and practical guidance for the development of a governance model matching with the characteristics of Chinese enterprises. Meanwhile, it will also add a new dimension to the academic research on the governance of commercial groups. Through literature review, this research presents a systematic review over the history of the traditional governance of Fujian commercial group. The theory of historical and comparative institutional analysis is employed to further analyze the governance mechanism of Fujian commercial group. As discovered in the research, the governance of Fujian commercial group is exogenously based on clan and township relationships, and closely related to the regional environment and culture of Fujian merchants. In the past, Fujian commercial group relied on the power of township relationships to foster successful businesses. Endogenously, Fujian merchants took a path of governance by combining long-termism with collectivism, which is absolutely distinct from the other commercial groups formed by Anhui (Hui) merchants, Shanxi (Jin) merchants, and other merchants. This choice reveals Fujian merchants’ unique mystery of sustainable development.On the basis of literature review, we interviewed nine owners and 23 professional managers of Fujian merchants’ enterprises for this research. After extensively analyzing the internal management and external operation strategies of modern Fujian merchants’ enterprises, we extracted the characteristics and mechanism of their governance. Additionally, we interviewed five other family enterprises to verify the characteristics of Fujian merchants’ governance mechanism. In this research, it is found that Fujian entrepreneurs were deeply affected by local culture and merchants’ belief of “inner ancestors and outer saints” in their corporate governance. Therefore, they embraced long-termism in the selection, appointment, management, motivation, and punishment of professional managers, but showed the effect of collectivism in their socializing with professional managers. With “trust, cooperation, and return” as the core of business, the Fujian merchants’ enterprises relied on relationship supported by contract in governance, and integrated the stewardship theory in the process of evolution. On this basis, they established an effective governance mechanism.Presently, the governance model of Fujian commercial group is still of great value to modern enterprises. With its trust-based governance structure and management strategy of collectivism and long-termism, it provides a governance model fit with the cultural environment in China for modern enterprises. The conclusions drawn in this research will not only make a significant theoretical contribution to understanding the governance model of Chinese enterprises, but also formulate a new approach to the establishment of corporate governance structure for practitioners, and provide reference for policymakers in their development of relevant policies. The extensive analysis on the governance model of Fujian merchants is provided in this research, but the generality of research findings may be undermined by the limited sample size. In the future, studies may increase the sample size and perform cross-cultural comparison to further verify and expand the conclusions of this research.